Evaluation of anti-rollback systems in manual wheelchairs: muscular activity and upper limb kinematics during propulsion - Bartosz Wieczorek; Mateusz Kukla; Łukasz Warguła; Marcin Giedrowicz; Dominik Rybarczyk (Scientific Reports, 2022)
Abstract Self-propelling a wheelchair up a hill requires intense muscular effort and introduces the risk of the wheelchair rolling down. The purpose of this paper was to assess the user's muscular activity during ramp climbing. Tests were carried out on a group of 10 subjects who had to propel a wheelchair up a standardized wheelchair ramp. Basic parameters of upper limb kinematics were measured to determine the total push-rim rotation angle. This was 105.91° for a wheelchair with a stiff anti-rollback system, 99.39° for a wheelchair without an anti-rollback system and 98.18° for a wheelchair with a flexible anti-rollback system. The upper limb muscle effort was measured at 55 ± 19% for the wheelchair without an anti-rollback system, 59 ± 19% for the wheelchair with a stiff anti-rollback system and 70 ± 46% for the wheelchair with a flexible anti-rollback system. The conducted research showed an increase in muscle effort while using anti-rollback systems. In the case of push-rim rotation angle, no significant differences in the value of the rotation angle were found.